Certain Subclass of m-Valent Functions Associated with a New Extended Ruscheweyh Operator Related to Conic Domains. (31st July 2021) - Shammaky, Amnah E.; Seoudy, Tamer M.
Abstract : The main object of the present paper is to introduce certain subclass of m -valent functions associated with a new extended Ruscheweyh linear operator in the open unit disk. Also, we investigate a number of geometric properties including coefficient estimates and the Fekete–Szegö type inequalities for this subclass. Several known consequences of the main results are also pointed out.